2016
DOI: 10.1021/acs.nanolett.6b04044
|View full text |Cite
|
Sign up to set email alerts
|

NaxMV(PO4)3 (M = Mn, Fe, Ni) Structure and Properties for Sodium Extraction

Abstract: NASICON (Na super ionic conductor) structures of NaMV(PO) (M = Mn, Fe, Ni) were prepared, characterized by aberration-corrected STEM and synchrotron radiation, and demonstrated to be durable cathode materials for rechargeable sodium-ion batteries. In NaMnV(PO), two redox couples of Mn/Mn and V/V are accessed with two voltage plateaus located at 3.6 and 3.3 V and a capacity of 101 mAh g at 1 C. Furthermore, the NaMnV(PO) cathode delivers a high initial efficiency of 97%, long durability over 1000 cycles, and go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
257
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(282 citation statements)
references
References 35 publications
15
257
0
Order By: Relevance
“…[30] Compared with Na 3 V 2 (PO 4 ) 3 , Na 4 MnV(PO 4 ) 3 also possesses higher voltage, lower cost, and lower toxicity, demonstrating promising prospects for applications. Recently, Goodenough's group substituted half of V in Na 3 V 2 (PO 4 ) 3 with other transition metals, fabricating a series of NASICON-structured Na x MV(PO 4 ) 3 (M = Fe, Mn, Ni) compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[30] Compared with Na 3 V 2 (PO 4 ) 3 , Na 4 MnV(PO 4 ) 3 also possesses higher voltage, lower cost, and lower toxicity, demonstrating promising prospects for applications. Recently, Goodenough's group substituted half of V in Na 3 V 2 (PO 4 ) 3 with other transition metals, fabricating a series of NASICON-structured Na x MV(PO 4 ) 3 (M = Fe, Mn, Ni) compounds.…”
mentioning
confidence: 99%
“…The Mn/ VO 6 octahedra is corner-shared with PO 4 tetrahedra to form [MnV(PO 4 ) 3 ] "lantern" units, and further establish a 3D framework with facile ion diffusion paths. [30,35] X-ray photoelectron spectroscopy (XPS) was used to identify the NMVP@C@ GA material. 3D ion diffusion channels are illustrated in Figure S4 (Supporting Information).…”
mentioning
confidence: 99%
“…Besides PO 4 polyanion unit's replacement, metal ion doping, either to sodium or to vanadium, is also demonstrated as an efficient strategy to enhance the efficiency and overall performance of NASICON‐based batteries . For example, the doping of K + to the Na + site in NVP can enhance the rate performance of Na 3 V 2 (PO 4 ) 3 due to the larger atomic size of K + than that of Na + , which can significantly enlarge the lattice volume along the c‐axis and thus increase the Na + diffusion pathway.…”
Section: Cathode Materialsmentioning
confidence: 99%
“…The metal doping to vanadium can affect the electrochemical performance of Na 3 V 2 (PO 4 ) 3 as well. Goodenough et al investigated a class of Na x MV(PO 4 ) 3 (M = Mn, Fe, Ni) obtained through transition metal substitution, and found the NASICON structure could be well maintained after repeated Na + extraction and insertion . Yang et al found that Mg 2+ doping did not change the structure of NVP, but could effectively improve ionic/electronic conductivity and obtain optimized particle size, thus enhancing the rate capability: the specific capacity only decreased from 112.5 to 94.2 mAh g −1 when the current density increased from 1 C to 30 C …”
Section: Cathode Materialsmentioning
confidence: 99%
“…[15,16] The V 4 + /V 3 + and Ti 4 + /Ti 3 + redox processes in vanadium-and titanium-based insertion hosts with the NASI-CON structure occur within the electrochemical stability window of water. [20][21][22][23][24][25] In consequence,a mphoteric insertion hosts that can be used as cathode and anode materials are being developed. Specifically,N aTi 2 (PO 4 ) 3 is of high interest because it is redox active at the lower end of the aqueous electrolyte stabilityw indow,w hicht hus enables enhanced energy densities.…”
Section: Introductionmentioning
confidence: 99%